DO SEEDS OF Anadenanthera macrocarpa AND Pityrocarpa moniliformis FORMED IN DIFFERENT LOCATIONS OF THE FRUIT HAVE SIMILAR PHYSIOLOGICAL QUALITY? - Silva, Priscilla Karine Barros da; Felix, Francival Cardoso; Medeiros, Josenilda Aprígio Dantas de; Araújo, Fernando dos Santos; Ferrari, Cibele dos Santos; Pacheco, Mauro Vasconcelos (Floresta, 2021)
Trees of the Fabaceae family can produce seeds with contrasting size and germinative performance depending on the region where they were formed in the fruit. Such differences reduce the physiological quality of the seed lot. Thus, the aim of the present study was to evaluate the physiological quality of seeds formed in different seminal nucleus of the fruits of Anadenanthera macrocarpa and Pityrocarpa moniliformis and their implications for the final composition of the seed lot. The biometric characterization of the fruits was performed with four quantitative descriptors (length, width, thickness, and number of seeds per fruit). Then, seeds formed in seminal nucleus of the proximal, intermediate, and distal regions of the fruit were measured (length, width, and thickness) and evaluated using germination and vigor tests (germination speed, length, and dry weight of seedlings). Seeds from these species have biometric differences depending on their origin in the fruit, in which those formed in the seminal nucleus of the intermediate region of the fruit are larger than the other ones. The origin of the seeds of A. macrocarpa and P. moniliformis formed in different seminal nucleus of the fruit do not show differences in physiological quality. Therefore, the sorting of seeds originated in different regions of the fruit does not benefit the final quality of the seed lots of these species.